Possibility of heat recovery from gray water in residential building - Mazur Aleksandra; Słyś Daniel (Selected Scientific Papers: Journal of Civil Engineering, 2017)
Recovery of waste heat from gray water can be an interesting alternative to other energy saving systems in a building, including alternative energy sources. Mainly, due to a number of advantages including independence from weather conditions, small investment outlay, lack of user support, or a slight interference with the installation system. The purpose of this article is to present the financial effectiveness of installations which provide hot, usable water to a detached house, using a Drain Water Heat Recovery (DWHR) system depending on the number of system users and the various combinations of bathing time in the shower, which has an influence on the daily warm water demand in each of the considered options. The economic analysis of the adopted installation variants is based on the Life Cycle Cost (LCC) method, which is characterized by the fact that it also includes the operating costs in addition to the capital expenditure during the entire analysis period. For each case, the necessary devices were selected and the cost of their installation was estimated.